Toll like receptor 4 facilitates invasion and migration as a cancer stem cell marker in hepatocellular carcinoma. Issue 2 (28th March 2015) - Liu, Wen-Ting; Jing, Ying-Ying; Yu, Guo-feng; Han, Zhi-peng; Yu, Dan-dan; Fan, Qing-Min; Ye, Fei; Li, Rong; Gao, Lu; Zhao, Qiu-Dong; Wu, Meng-Chao; Wei, Li-Xin
Highlights: TLR4 expression was associated with the ability of invasion and migration in HCC. TLR4 expression contributes to the stem-like properties of HCC cells. The high expression of TLR4 is associated with clinicopathological characteristics and prognosis of HCC. Abstract: Cancer stem cells (CSCs) or tumor-initiating cells (TICs), a small subset of tumor cells, are involved in tumor initiation, progression, recurrence and metastasis. In human hepatocellular carcinoma (HCC), TICs are enriched with cell surface markers and play a key role in chemotherapy resistance, tumor invasion and migration. Toll like receptor 4 (TLR4), acting as a receptor for lipopolysaccharide (LPS), has been reported to be responsible for carcinogenesis, invasion, metastasis and cancer progression. In our study, two HCC cell lines and a splenic vein metastasis of the nude mouse model were used to study the invasive ability of TLR4 positive HCC cells in vitro and in vivo . Stem-like features were also detected in TLR4 positive HCC cells. A total of 88 clinical samples from HCC patients were used to evaluate the association of TLR4 and stem-cell marker expression, and the relationship between TLR4 expression and clinicopathological characteristics was analyzed. The in vitro and in vivo experiments indicated that TLR4 positive HCC cells displayed significantly enhanced invasion and migration, and stem-like properties were also detected in TLR4 positive HCC cells. Clinically, TLR4 expression levels were found to be significantly higher in HCC tissues with microvascular invasion. Additionally, high expression of TLR4 in HCC tissues was strongly associated with both early recurrence and poor survivals in patients. Our results indicated that there was a relationship between TLR4 expression and CSC's features, TLR4 may act as a CSC marker, prompting tumor invasion and migration, which contributes to the poor prognosis of HCC.